THE IMPLEMENTATION OF PROJECT BASED LEARNING (PJBL) MODEL TO IMPROVE THE SIXTH GRADERS’ NATURAL SCIENCE CONCEPT UNDERSTANDING ON SIMPLE ELECTRICAL CIRCUIT MATERIALS AT SDN 3 PABEAN ILIR - Febri Ari Ramdhani; Asep Samsudin; Uus Kuswendi; Muhammad Rizal Fauzi (Sekolah Pascasarjana UPI, 2022)
ABSTRACTThis study aims to examine one of the ways to increase the understanding of the science concept of class VI UPTD SDN 3 Pabean Ilir students on electrical circuit material. The type of research used is classroom action research consisting of two cycles. The stages of this research consisted of four stages, namely planning, action, observation, and reflection. The subjects in this study were students of class VI UPTD SDN 3 Pabean Ilir. The instrument in this study was a science concept understanding test. The data obtained from this study during the pre-cycle mean the test scores for students' understanding of science concepts during the pre-cycle were 71.64. In cycle I, the average score for students' understanding of science concepts was 77.92. In cycle II, the average score for students' understanding of science concepts was 88.42. It can be concluded that this study shows that the application of the project based learning (PjBL) model can improve students' understanding of science concepts in class VI on electrical circuits.